Descemet Membrane Endothelial Keratoplasty Learning Curve for Graft Preparation in an Eye Bank Using 645 Donor Corneas. Issue 6 (June 2018) - Parekh, Mohit; Ruzza, Alessandro; Romano, Vito; Favaro, Elisa; Baruzzo, Mattia; Salvalaio, Gianni; Grassetto, Andrea; Ferrari, Stefano; Ponzin, Diego
Abstract : Purpose: To investigate the learning curve of Descemet membrane endothelial keratoplasty (DMEK) graft preparation in an eye bank. Methods: Four operators prepared 645 DMEK grafts using the stripping technique between 2014 and 2017 at the Veneto Eye Bank Foundation, Italy. Endothelial cell loss (ECL) and tissue wastage were recorded retrospectively after DMEK preparation and correlated with the number of tissues prepared each year by each operator. On average, our operators performed 1 donor preparation a week over the course of this study. Only donors older than 60 years were used in this study, and approximately 10% of donors had diabetes. The Wilcoxon test for paired data and 1-way ANOVA were used for checking statistical significance with the Tukey test as post hoc analysis. P < 0.05 was considered statistically significant. Results: ECL did not change significantly over time from operator 1. Significant ECL drop was noted from operator 2 between years 2014–2016 ( P = 0.0049) and 2017 ( P = 0.0094); from operator 3 between years 2015–2016 ( P = 0.0288) and 2017 ( P = 0.0097); and from operator 4 between 2015–2016 ( P = 0.0469) and 2017 ( P = 0.0331). Operators 1 and 3 did not show a significant difference, considering every 50 grafts prepared by each operator. Operator 2 showed significant ECL drop between 1 to 50 and 51 to 100 ( P = 0.0002) and 1 to 50 and 101 to 150 ( P = 0.0001) grafts. Operator 4 showed significant ECL drop between 1 to 50 and 101 to 150 ( P = 0.002) and 51 to 100 and 101 to 141 ( P = 0.0207) grafts. No intraoperator difference was observed per 50 grafts ( P > 0.05). Conclusions: There is a learning curve for DMEK graft preparation. ECL and tissue wastage can be reduced with practice and skills. However, each operator may be limited to his or her own learning capability.